Teachers' Creativity in Teaching Islamic Religious Education and Its Impact on Students' Learning Interests - Maryam Hulinggi; Lamsike Pateda; Suharia Sarif (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the creativity of Islamic Religious Education teachers in teaching and its relation to the learning interests of grade VII students at Muhammadiyah Pone Junior High School. Methodology: This study uses a qualitative approach with a case study type to gain an in-depth understanding of creative learning strategies carried out by Islamic Religious Education teachers in the school context. Data was collected through in-depth interviews with teachers, students, and principals, direct observation in teaching and learning activities, and analysis of supporting documents such as learning implementation plans and evaluation notes. Data analysis was carried out using data reduction techniques, data presentation, and interactive conclusion drawn. The research procedure includes the preparation stage (determining the focus of the problem and research permits), the stage of data collection in the field, the stage of repeated analysis to find creative learning patterns, to the stage of verifying findings through triangulation of sources and methods. Main Findings: The results of the study show that Islamic Religious Education Teachers apply various creative approaches, such as the use of Islamic stories, simulations of worship practices, visual media, and contextual discussions related to students' daily lives. Novelty/Originality of this study: Islamic Religious Education learning that is managed creatively, with the support of the principal, is able to foster student involvement and interest in learning in a more meaningful way, so that grade VII students have high enthusiasm, activeness in class, and positive learning interest in Islamic Religious Education subjects.